Craniofacial Surgery for Esthesioneuroblastoma: Report of an International Collaborative Study - Patel, Snehal G.; Singh, Bhuvanesh; Stambuk, Hilda E.; Carlson, Diane; Bridger, Patrick G.; Cantu, Giulio; Cheesman, Anthony D.; Donald, Paul; Fliss, Dan; Gullane, Patrick; Kamata, Shin-etsu; Janecka, Ivo; Kowalski, Luiz P.; Kraus, Dennis H.; Levine, Paul A.; Medina, Luiz R.; Pradhan, Sultan; Schramm, Victor; Snyderman, Carl; Wei, William I.; Shah, Jatin P. (Journal of Neurological Surgery Part B: Skull Base, 2012)
Introduction Impact of treatment and prognostic indicators of outcome are relatively ill-defined in esthesioneuroblastomas (ENB) because of the rarity of these tumors. This study was undertaken to assess the impact of craniofacial resection (CFR) on outcome of ENB.Patients and Methods Data on 151 patients who underwent CFR for ENB were collected from 17 institutions that participated in an international collaborative study. Patient, tumor, treatment, and outcome data were collected by questionnaires and variables were analyzed for prognostic impact on overall, disease-specific and recurrence-free survival. The majority of tumors were staged Kadish stage C (116 or 77%). Overall, 90 patients (60%) had received treatment before CFR, radiation therapy in 51 (34%), and chemotherapy in 23 (15%). The margins of surgical resection were reported positive in 23 (15%) patients. Adjuvant postoperative radiation therapy was used in 51 (34%) and chemotherapy in 9 (6%) patients.Results Treatment-related complications were reported in 49 (32%) patients. With a median follow-up of 56 months, the 5-year overall, disease-specific, and recurrence-free survival rates were 78, 83, and 64%, respectively. Intracranial extension of the disease and positive surgical margins were independent predictors of worse overall, disease-specific, and recurrence-free survival on multivariate analysis.Conclusion This collaborative study of patients treated at various institutions across the world demonstrates the efficacy of CFR for ENB. Intracranial extension of disease and complete surgical excision were independent prognostic predictors of outcome.
Keywords: nose neoplasms/mortality/pathology/surgery/*therapy; esthesioneuroblastoma; olfactory/*therapy; combined modality therapy; radiotherapy; adjuvant; survival analysis